Zur temporalen Entfaltung und multimodalen Orchestrierung von konzeptuellen Räumen am Beispiel einer Erzählung - Ladewig, Silva; Hotze, Lena (Linguistik Online, 2020)
The study presented in this article investigates the temporal unfolding and multimodal orchestration of meaning in a narration. Two aspects are focused on. First, the temporal and multimodal orchestration of conceptual spaces in the entire narrative is described. Five conceptual spaces were identified which were construed by multiple visual-kinesic modalities and speech. Moreover, the study showed that the conceptual spaces are often created simultaneously, which, however, does not lead to communication problems due to the media properties of the modalities involved (see also Schmitt 2005). The second part of the analysis zoomed in onto the phase of the narrative climax in which the multimodal production of the narrative space with role shift dominated. By applying a timeline-annotation procedure for gestures (Müller/Ladewig 2013) a temporally unfolding salience structure (Müller/Tag 2010) could be reconstructed which highlights certain semantic aspects in the creation and flow of multimodal meaning. Thus, specific information “necessary” to understand the climax of the narration was foregrounded and made prominent for a co-participant. By focusing methodically and theoretically on the temporal structure and the interplay of different modalities, the paper offers a further contribution to the current discussion about temporality, dynamics and multimodality of language (Deppermann/Günthner 2015; Müller 2008b).